If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Solution for (Y-k)h=c equation:
(Y + -1k) * h = c
Reorder the terms for easier multiplication:
h(Y + -1k) = c
(Y * h + -1k * h) = c
(hY + -1hk) = c
hY + -1hk = c
Solving for variable 'h'.
Move all terms containing h to the left, all other terms to the right.
Reorder the terms:
-1c + hY + -1hk = c + -1c
Combine like terms: c + -1c = 0
-1c + hY + -1hk = 0
The solution to this equation could not be determined.